Prevalence and control of Aspergillus spp. and aflatoxins in peanut sauce during food processing - Abdul Halim, Farawahida (2017)
Peanut sauce is one of Malaysian cooking dishes which is mass-produced by several companies. Peanut sauce is usually made of peanuts and chili, and these commodities are normally contaminated with Aspergillus spp. and aflatoxins (AFs). Unfortunately, the safety of peanut sauce is not always assured as the processing line is not controlled (especially those of small enterprises). Hence, the first objective of this study was to determine the prevalence of Aspergillus spp. and AFs along processing steps of peanut sauce manufactured by different companies. Samples were collected from each step of peanut sauce processing at three peanut sauce companies (A, B, and C). Media used to identify A. flavus and A. parasiticus was A. flavus and A. parasiticus agar (AFPA), meanwhile AFs were analyzed by using High-performance Liquid Chromatography with a multi λ fluorescence detector (HPLC-FLD). None of the samples from Company A were contaminated with AFs and Aspergillus spp. 12.5% of the samples from Company B were contaminated with Aspergillus spp. and exceeded the limit. Meanwhile, 87.5% of the samples were contaminated with AFs (0.58 – 32.91 ng/g), with 12.5% of them exceeded the permissible limit. For Company C, 37.5% of the samples were contaminated with Aspergillus spp. and exceeded the limit (log 3.44 - 5.05 CFU/g). Meanwhile, all the samples were contaminated with AFs (1.71 – 537.09 ng/g), with 75% of them exceeded the permissible limit. The steps in reducing AFs significantly in the peanut sauce were (i) safety monitoring of raw materials, (ii) sorting of peanut kernels, and (iii) heat treatment of peanut kernels (oil-less frying or frying) and cooking of chili paste or peanut sauce. The second objective of the present study was to control the practices for the reduction of AFs hazards and the effect of interventions in peanut sauce processing. Company C was chosen to fulfill this objective because the level of total AFs in the samples was the highest compared to other companies. Four designs of processing steps were set up and samples were collected according to these designs: (1) control; (2) oil-less frying of chili powder; (3) addition of retort processing; (4) combination of oil-less frying of chili powder and retort processing. Designs 2 and 4 reduced Aspergillus spp. significantly in oil-less fried chili powder (from log 3.26 to <3.00 CFU/g), and Design 4 reduced Aspergillus spp. in peanut sauce by 15% (from log 3.62 to 3.08 CFU/g). Meanwhile, Design 2 reduced total AFs by 33% (from 19.98 to 13.48 ng/g), Design 3 reduced total AFs in peanut sauce by 49% (from 363.35 to 184.34 ng/g), while Design 4 significantly reduced total AFs in oil-less fried chili and peanut sauce by 41% (from 30.00 to 17.60 ng/g) and 57% (from 384.74 to 164.62 ng/g), respectively. This study proved that oil-less frying of chili powder, retort processing, and a combination these processes significantly reduce AFs levels. Design 4 (combination of oil-less frying of chili powder and retort processing) yielded the highest reduction of total AFs and therefore recommended to be employed by the Company C.